Knowledge, attitude, and practice toward pediatric vitamin D deficiency among parents - Yu, Chunli; Cai, Jingjuan; Wang, Chunxiang; Luo, Yan; Fang, Jian (Frontiers in Pediatrics, 2024)
Objective To investigate the knowledge, attitude, and practice (KAP) towards pediatric vitamin D deficiency (VitD) among parents and explore the risk factors of their knowledge, attitude, and practice. Methods This cross-sectional study enrolled parents in our Hospital between November 2022 and January 2023. Results A total of 621 valid questionnaires were collected in this study. The knowledge, attitude, and practice scores were 6.13 ± 3.07 (theoretical score range: 0–13), 31.13 ± 6.20 (theoretical score range: 9–45), and 27.47 ± 4.21 (theoretical score range: 9–45), respectively; the mean knowledge score was <60%, indicating poor knowledge. Commercial and service industry workers and a monthly income ≥5,000 CNY were independently associated with sufficient knowledge (all P < 0.05). The knowledge score, ethnic minorities, divorced/widows, and spouses with a master's degree or above were independently associated with positive attitudes (all P < 0.05). The attitude score, female, non-urban, undergraduate education, commercial and service industry worker, and office worker were independently associated with proactive practice (all P < 0.05). Those characteristics could help design future KAP interventions on vitD deficiency. Conclusions This study demonstrated poor knowledge, positive attitude, and proactive practice regarding pediatric VitD deficiency among parents. Targeted interventions and educational programs should be developed to improve parental knowledge.